Optimizing Brand Awareness and Purchase Intention Travel Agents: Communication Strategy through Social Media Marketing - Senalasari, Widi; Setiaji, Mara; Khrisnamurti, Nino; Februadi, Agustinus (Journal of Marketing Innovation (JMI), 2024)
High demand of tourism services in Indonesia has increased the number of travel agency businesses. However, conventional travel agencies must face difficulties by competing with Online Travel Agents (OTAs). This study aims to investigate the impact of communication strategy using the AIDA model on social media marketing strategies in enhancing brand awareness of traditional travel agencies and purchase intention. 420 respondents who have acquired conventional travel agency services via social media filled out the e-questionnaire and became the sample of this study. Data analysis was done using the partial least square structural equation modeling (PLS-SEM) method. This study found a positive relationship between communication strategy using the AIDA model and its impact on social media marketing. A positive correlation between brand awareness and purchase intention to social media marketing was also found. The findings of this research can be utilized by traditional travel agents to reorganize their marketing strategies through social media to increase brand awareness and purchase intention so that they will be able to compete with OTAs.